Diagnostic value of radiography and ultrasound for suspected acute hematogenous osteomyelitis - S. A. Polkovnikova; V. D. Zavadovskaya; V. M. Mashkov (Вестник рентгенологии и радиологии)
Objective: to evaluate the informativeness of ultrasonography and radiography in the early diagnosis of acute hematogenous osteomyelitis in children.Material and methods. Children (from 3 weeks to 1 year old) with suspected acute hematogenous osteomyelitis (n = 40) were examined and X-rays and ultrasound scan of the affected skeleton were performed. 39 (97.5%) of children underwent surgery.Results. Radiography in the first 3 days of the disease gave only false-negative results. On the 5th-7th day of the disease, the fuzziness of the outline of the growth zone, the uneven contour of the ossification core, was found, which resulted in 33% sensitivity. X-ray symptoms of bone destruction were obtained in the second week of the disease in 83% of the subjects.The results of ultrasound examination in the first 3 days of the disease exceeded the radiographic parameters and corresponded to 66.7% of sensitivity based on the definition of increased vascularization of edematous parasal soft tissues, epiphyseal cartilage. On the 5th-7th days of the disease, local hyperechoic areas were found in the epiphyseal cartilage, with additional color signals around it, an uneven contour of the ossification nucleus, which almost equalized the sensitivity parameters of X-ray and ultrasound studies (83.33% and 88.8%, respectively).The most sensitive, specific and accurate are the studies in the third week from the onset of the disease, in determining the sites of destruction in the metaphysis and the nucleus of ossification of the epiphysis, both in X-ray and ultrasound studies.Conclusion. X-ray and ultrasound studies should be considered complementary modalities for obtaining optimally complete information about the morphological substrate of the pathological inflammatory process.